Reflection of Women´s Roles in British Society in A Clockwork Orange by Anthony Burgess - Skalecká, Kamila (Univerzita Pardubice, 2014)
This thesis aims to analyse the reflection of women's roles in the British society in A Clockwork Orange by Anthony Burgess. Based on the cultural and historical analysis focusing on the consequences of the British Welfare State, the paper attempts to link the features of the British society to the novel. The basic definitions of feminism and feminist literary theory are then introduced and confronted with the aspects of the Burgess's novel in order to find out in what ways the novel reinforces patriarchal ideology.
Odraz role ženy v britské společnosti v románu Mechanický pomeranč Anthony Burgesse
Keywords: Mechanický pomeranč; Burgess, Anthony; britská společnost; sociální stát; ženy; patriarchát; Clockwork Orange; Anthony Burgess; British society; Welfare State; women; patriarchy